Palm oil mill fly ash as a low-cost adsorbent for Rhodamine-B removal from industrial wastewater. Issue 1 (May 2020) - Pinem, J A; Utama, P S; Irianty, R S; Prawiranegara, B A; Saputra, Edy
Abstract: In this study, the adsorption properties of Rhodamine-B (RB) on fly ash were investigated. Two different fly ashes conditions, including raw fly ash and activated fly ash, were selected for the adsorption experiment. The adsorption process is conducted by mixing fly ash 0.5; 1; 1, 5 and 2g/L with the temperature of 30°C; 35°C; 45°C. The results showed that the HCl activation will enhance the MB adsorption capacity of fly ash, the higher the mass of adsorbent, and the higher mixing temperature, the better the performance of adsorbent is. Then, the great conditions for reducing RB with adsorbent mass 2g/L at temperature of 45°C, with a removal efficiency 90, 54%